From Building Blocks to Case Studies: Estimating the Costs of Transport and Storage for East Coast Australia. (July 2017) - Neal, P.R.; Ho, M.T.; Weihs, G.A. Fimbres; Wiley, D.E.
Abstract: CCS presents the opportunity to utilise Australia's coal and gas resources in an emissions constrained world. Through this study, we have undertaken the most comprehensive assessment to date of the practical equipment costs associated with transporting and storing CO2 captured from power plants in Australia. The implementation of CCS in Australia will require a large transport and storage network involving pipelines, booster pumps, wells, storage site facilities and storage site monitoring. Such a network does not currently exist and needs to be built if CCS is to be deployed at scale. Excluding initial compression, the total plant costs for transport and storage of CO2 from power plant emission hubs in Australia are estimated to vary from as little as 5-14/t injected for cases with short transport distance and good quality storage sites up to about 60/t injected for transport of large volumes of CO2 over long distances to lower quality sites. These costs should not be confused with total project costs that include additional owner's costs of at least 15-40% for proving up storage sites, undertaking the required front end engineering and obtaining project approvals. The total project costs may also require extra risk-adjusted costs.